2022
DOI: 10.3390/fishes7040209
|View full text |Cite
|
Sign up to set email alerts
|

First Evaluation of Associated Gut Microbiota in Wild Thick-Lipped Grey Mullets (Chelon labrosus, Risso 1827)

Abstract: This study aimed to characterize the intestinal microbiota of wild thick-lipped grey mullets (Chelon labrosus) and explore its potential functionality on the host. Intestinal contents of anterior and posterior sections from wild fish were collected and DNA was extracted. Subsequently, the V3–V4 regions of 16S rRNA were sequenced using the Illumina technology and results were analyzed by bioinformatics pipeline. The functional profile of the microbial community was analyzed using PICRUSt software. Shannon and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 90 publications
2
6
0
Order By: Relevance
“…culture of grey mullets Mugilidae species is considered a priority within the current strategies of sustainable European aquaculture [21]. To the authors' knowledge, various studies were made on the gut microbiota of cultured [41] and wild mullets [23,31] and the present study has provided more information on the biodiversity of this ecosystem and their biotechnological potential. Previous studies on Mediterranean grey mullets had showed some interesting biotechnologically traits of intestinal cultivable bacteria as a source of bioactive compounds with immunological and bioremediation functions [42].…”
Section: Familiesmentioning
confidence: 83%
See 3 more Smart Citations
“…culture of grey mullets Mugilidae species is considered a priority within the current strategies of sustainable European aquaculture [21]. To the authors' knowledge, various studies were made on the gut microbiota of cultured [41] and wild mullets [23,31] and the present study has provided more information on the biodiversity of this ecosystem and their biotechnological potential. Previous studies on Mediterranean grey mullets had showed some interesting biotechnologically traits of intestinal cultivable bacteria as a source of bioactive compounds with immunological and bioremediation functions [42].…”
Section: Familiesmentioning
confidence: 83%
“…In particular, members of Chloroflexi phylum belonging to the Anaerolineaceae family, found at an abundance of more than 6% in the mullets collected in autumn, are described in literature as methano-genic bacteria (hydrocarbon degrading), frequently encountered in presence of petroleum. The presence of bacteria able of degrading toxic substances as aromatic compounds (sty-rene and fluorobenzoate) on Chelon labrosus was also pointed out by means of PICRUSt functional analysis [23], although their role is still unclear and most of this group of microorganisms remains uncultured and understudied [49].…”
Section: Familiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Microbial metabolic pathway analysis using PICRUSt is mostly suggested in association with carbohydrates, protein, amino acids, energy metabolism, membrane transport, nutrient digestion, immune function, and xenobiotic metabolism within the fish gut ( García-Márquez et al, 2022 ). Feeding habits and trophic levels of fish are important factors to determine parts of the gut microbe community.…”
Section: Discussionmentioning
confidence: 99%